Diplomasi Middle-Power Indonesia di Masa Pandemi - Albert Triwibowo; Jessica Martha (Indonesian Perspective, 2021)
Middle countries are considered to be more vulnerable in crisis management because of their marginal position in the international politics. In the pandemic, middle power diplomacy is expected to fill the void left by developed countries so that they focus on multilateral efforts. This paper argues that Indonesia exercised middle power diplomacy in 2020. This diplomacy is carried out with a commitment to encourage global cooperation in resolving the pandemic through multilateral efforts. The multilateral initiatives are carried out as part of ‘good international citizenship’, and also serves as the mechanism to voice Indonesian aspirations, aspirations related to humanity, efforts to create global norms, and efforts to reach international treaties. This paper is a qualitative research, which is based on a literature study in the form of an official statement from the Government of Indonesia through the Ministry of Foreign Affairs and is supported by secondary sources.